A Case Study on Personal Problems of Grade 10 Students at Sint Carolus Catholic Senior High School, Kupang, Associated with Online Game Addiction - Atawolo, Portunatus Mura; Nagul, Wens (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to determine the impact of online game addiction on the personal problems of a tenth-grade student at SMA Katolik Sint Carolus Kupang. The research subject was a tenth-grade student with the initials JP who exhibited online game addiction behaviors along with various personal and academic problems. This study employed a qualitative approach using a case study method. Data collection techniques included observation, interviews, and documentation, involving the student, homeroom teacher, subject teachers, guidance and counseling teacher, and the student’s guardian. Data validity was ensured through source and technique triangulation. Data analysis was conducted through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results indicate that online game addiction has an impact on decreased discipline, increased dishonest behavior, frequent school absenteeism, and the emergence of impolite behavior during the learning process. The contributing factors originate from internal aspects of the student, such as uncontrolled freedom and boredom, as well as external factors including peer influence, excessive gadget use, lack of parental supervision, and easy access to the internet. Intervention was carried out through individual counseling using a behavioristic approach with modeling techniques to develop positive student behavior.